Spatial and temporal variability of aerobic anoxygenic photoheterotrophic bacteria along the east coast of Australia - Jaime Bibiloni‐Isaksson; Justin R. Seymour; Tim Ingleton; Jodie van de Kamp; Levente Bodrossy; Mark V. Brown (Environmental Microbiology, 2016)
Summary Aerobic Anoxygenic Phototrophic Bacteria (AAnPB) are ecologically important microorganisms, widespread in oceanic photic zones. However, the key environmental drivers underpinning AAnPB abundance and diversity are still largely undefined. The temporal patterns in AAnPB dynamics at three oceanographic reference stations spanning at approximately 15° latitude along the Australian east coast were examined. AAnPB abundance was highly variable, with pufM gene copies ranging from 1.1 × 10 2 to 1.4 × 10 5 ml −1 and positively correlated with day length and solar radiation. pufM gene Miseq sequencing revealed that the majority of sequences were closely related to those obtained previously, suggesting that key AAnPB groups are widely distributed across similar environments globally. Temperature was a major structuring factor for AAnPB assemblages across large spatial scales, correlating positively with richness and Gammaproteobacteria (phylogroup K) abundance but negatively with Roseobacter‐clade (phylogroup E) abundance, with temperatures between 16°C and 18°C identified as a potential transition zone between these groups. Network analysis revealed that discrete AAnPB populations exploit specific niches defined by varying temperature, light and nutrient conditions in the Tasman Sea system, with evidence for both niche sharing and partitioning amongst closely related operational taxonomic units.